A creep-resistant high-thermal-conductivity graphene-modified high-speed steel material and a preparation method thereof
By using creep-resistant high-thermal conductivity graphene modified high-speed steel material as heating plate in thermal bending equipment, the problem of insufficient performance of the 310S stainless steel heating plate at high temperatures is solved, and the effects of high hardness, excellent thermal conductivity and small thermal expansion coefficient are achieved, and the accuracy and production efficiency of the thermal bending system are improved.
Patent Information
- Application Number
- CN202310376370.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-04-11
AI Technical Summary
The 310S stainless steel heating plate used in existing thermal bending equipment has problems such as low hardness, low thermal conductivity, large thermal expansion coefficient and easy oxidation at high temperatures, resulting in limited accuracy and production efficiency of the thermal bending system.
The high-speed steel material of high-cream resistance to high-thermal conductivity graphene is used as the heating plate. Through the coordinated strengthening of the intermetallic compounds generated in situ and graphene, the high-temperature hardness, thermal conductivity and stability of the material are improved.
It achieves high hardness, excellent thermal conductivity and small thermal expansion coefficient of the material, improves the accuracy and production efficiency of the thermal bending system, reduces creep deformation, and has good oxidation resistance.
Smart Images

Figure CN116445830B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-speed steel material, in particular to a creep-resistant high-thermal-conductivity graphene-modified high-speed steel material and a preparation method thereof, and belongs to the field of special alloy preparation. Background Art
[0002] With the vigorous development of industries such as home building materials, information optoelectronics, automobile industry and smart devices, 3D curved glass has attracted much attention due to its unique optical properties, thermal stability and mechanical properties. For example, in the field of smart phones, 3D curved glass is widely used in high-end mobile phone models because of its thinness, transparency and cleanliness, fuller visual effects and more ergonomic touch feel. Relevant data show that the penetration rate of 3D glass cover plates for smart phones is increasing year by year, reaching about 27% in 2020, and the future market size is expected to be promising. At the same time, 3C product designs such as tablet computers, head-mounted VR devices, wearable smart products such as smart watches, vehicle central control and portable instrument panels have all seen the application of 3D glass, which has led to the continuous increase in market demand and precision requirements for 3D glass, thereby driving the development of the entire industry chain. However, due to its special and complex geometric dimensions, the processing difficulty of 3D curved glass is much higher than that of ordinary flat glass.
[0003] At present, 3D curved glass is mainly prepared by cold processing and hot forming technology, but the expensive equipment cost and long processing cycle of cold processing technology limit its application in the field of small size and large output of civilian demand. The widely used hot forming technology is to process the heated high viscoelastic state glass into shape by pressure processing through a forming mold, so as to prepare curved glass with high shape and dimensional accuracy. The core equipment of hot forming is the 3D hot bending glass machine. The hot bending process can be summarized as the heating tube heating to provide a heat source, and the heat and pressure are transferred to the glass through the heating plate, the heat plate, and the mold in turn, so as to complete the hot bending forming. Obviously, the heating plate is the initial component for heat and force transfer in the hot bending forming process. Its temperature control accuracy, temperature uniformity, force transfer uniformity and other properties determine the accuracy of the entire hot bending system and hot bending products. However, the 310S stainless steel (or similar grades) heating plate used in the current hot bending equipment has the problems of low high temperature hardness, low thermal conductivity and large thermal expansion coefficient. The thermal conductivity of 310S at room temperature is only 12-15W / (mk), the heat transfer rate is slow, the temperature field uniformity is limited, and the burden on the heating tube is increased; compared with other components of the heating system, the thermal expansion coefficient of 310S is much higher than that of the heat spreader and mold that are solidified with it. At high temperatures, the mismatch of thermal expansion coefficients causes deformation, and it is difficult to ensure high plane accuracy during long-term use; at the same time, the service hardness of 310S under long-term high temperature conditions is extremely low, and the hardness is as low as 10HRC or less when used at 600℃~900℃. The material is very easy to soften and cause creep deformation. In summary, the 310S heating plate adds uncertainty and instability to the hot bending system, which cannot further improve the accuracy of the equipment and limits production efficiency. However, no other suitable alternative materials have been found in the industry. In addition, since the heating plate material usually serves in a high temperature environment above 600℃, the problem of high-temperature oxidation of the material must also be considered. Therefore, there is an urgent need for a new heating plate material with high thermal conductivity, high high-temperature hardness, small thermal expansion coefficient and good oxidation resistance. Summary of the invention
[0004] In view of the problems existing in the prior art, the first purpose of the present invention is to provide a creep-resistant and highly thermally conductive graphene-modified high-speed steel material. The high-speed steel material is based on the synergistic effect between the components and utilizes in-situ generated intermetallic compounds and dispersed graphene for synergistic strengthening. While ensuring the high-temperature hardness of the material, the strength, stability and thermal conductivity of the material are greatly improved.
[0005] The second object of the present invention is to provide a method for preparing a creep-resistant and highly thermally conductive graphene-modified high-speed steel material. The method fully mixes graphene with other metal raw materials through batch dispersion and high-energy ball milling to improve the sintering activity of the material, and then promotes the uniform precipitation of nano-scale intermetallic compounds through heat treatment, thereby improving the strength and toughness of the material.
[0006] To achieve the above technical objectives, the present invention provides a creep-resistant and high thermal conductivity graphene-modified high-speed steel material, comprising the following elements in mass percentage: Co 15-30%, the total amount of Mo and W is 10-20% and the W content is less than 8%, Cr 5-10%, Ni 5-7%, Al 5-8%, Si 1.5-2%, V 0.5-1%, Ta 0.5-1%, Ce 0.1-0.3%, Sc0.1-0.2%, graphene is 0.5-1.5%, and the balance is iron.
[0007] The intermetallic compound in the creep-resistant high-thermal-conductivity graphene-modified high-speed steel material provided by the present invention is in-situ generated by elements such as Fe, Co, Mo, W, Cr, and Al. Compared with the carbide-reinforced phase in the traditional high-speed steel, the intermetallic compound is not easy to aggregate and over-age at high temperature, and maintains a coherent / semi-coherent interface relationship with the α-Fe matrix, which gives it high high-temperature hardness, excellent thermal conductivity, small thermal expansion coefficient, and good toughness. At the same time, an appropriate amount of graphene material is added to the intermetallic compound-reinforced high-speed steel matrix, and the characteristics of high strength, high thermal conductivity, and high stability of graphene are utilized to further enhance the toughness, thermal conductivity, and oxidation resistance of the high-speed steel material.
[0008] As a preferred solution, the high-speed steel material contains the following elements in mass percentage: Co18-27%, the total amount of Mo and W is 13-18% and the W content is less than 6%, Cr 7-10%, Ni 5-7%, Al 6-8%, Si 1.5-2%, V0.5-1%, Ta 0.5-1%, Ce 0.1-0.3%, Sc 0.1-0.2%, graphene is 1-1.5%, and the balance is Fe; the high-speed steel material includes an in-situ strengthening phase composed of intermetallic compounds and highly dispersed graphene.
[0009] In the high-speed steel material provided by the present invention, the addition amount of Mo and W elements must be strictly controlled according to the above requirements. Since W has a higher melting point and a larger specific gravity, when the W content is high, the temperature required for sintering and heat treatment is higher, which means more energy consumption and higher cost, and is not conducive to the demand for lightweight.
[0010] As a preferred solution, the intermetallic compound is an A7B6 type and / or AB2 type intermetallic compound.
[0011] As a preferred solution, the graphene is nickel-plated graphene.
[0012] The present invention uses nickel-plated graphene as the graphene raw material, which can minimize the interaction with iron at high temperature, ensure the integrity of graphene, and have good interface wettability. In the composite high-speed steel material, graphene inhibits grain growth and hinders dislocation movement to strengthen the material and improve mechanical properties. On the other hand, it enhances the thermal conductivity of the overall material through its own extremely high thermal conductivity (about 5000W / (m·K)).
[0013] The present invention also provides a method for preparing creep-resistant high-thermal-conductivity graphene-modified high-speed steel material, which comprises dispersing graphene in a ball milling medium, adding the remaining metal element powder for further dispersion, and then ball milling and drying with an auxiliary agent in sequence to obtain a mixture.
[0014] As a preferred solution, the mixed material is screened, cold pressed, sintered and heat treated in sequence to obtain the product.
[0015] As a preferred solution, the dispersion method is ultrasonic dispersion, and the conditions are: ultrasonic power is 100-200W, and the time is 20-40min. The preparation method provided by the present invention can achieve uniform dispersion of graphene raw materials and metal mixed powders, and obtain a graphene-reinforced composite material with high density and uniform tissue distribution.
[0016] As a preferred solution, the ball milling medium is at least one of water, ethanol, propanol and petroleum ether.
[0017] As a preferred solution, the ball milling medium is ethanol.
[0018] As a preferred solution, the ball milling method is wet high-energy ball milling, and its conditions are: under a protective atmosphere, the ball-to-material ratio is 4 to 7:1, the rotation speed is 240 to 340 r / min, and the time is 72 to 96 h; the protective atmosphere is high-purity nitrogen and / or high-purity argon.
[0019] As a preferred solution, the added amount of the carbon black accounts for 0.2-0.5% of the mass percentage of the mixed material.
[0020] In the present invention, carbon black is added in order to react with the adsorbed oxygen to produce a carbon-oxygen reaction during the sintering process. Its role is to reduce the impurity oxygen content of the material on the one hand, and to expose fresh atoms on the surface of the powder through the carbon-oxygen reaction on the other hand, thereby increasing the sintering driving force. However, it should be noted that the carbon black will be completely consumed during the sintering process and does not participate in the composition of the final product.
[0021] As a preferred solution, the molding agent is at least one of paraffin, PEG and PVB.
[0022] As a preferred solution, the added amount of the molding agent accounts for 3-6% of the mass percentage of the mixture.
[0023] As a preferred solution, the particle size of the material obtained by screening the mixed material is ≤40 mesh.
[0024] As a preferred solution, the cold pressing pressure is 100-200 MPa.
[0025] As a preferred solution, the sintering is programmed temperature vacuum sintering.
[0026] As a preferred solution, the sintering conditions are: heating from room temperature to 1300-1400°C at a rate of 5-10°C / min, keeping the temperature for 2-4h, and the vacuum degree ≤0.01Pa.
[0027] As a preferred solution, the heat treatment includes solution treatment and aging treatment.
[0028] As a preferred solution, the conditions of the solution treatment are: at 1150-1250°C, keeping warm for 0.5-1.5h, and cooling to room temperature by gas quenching.
[0029] As a preferred solution, the aging treatment conditions are: in a protective atmosphere, the temperature is 700-1000°C, the time is 3-5 hours, and the furnace is cooled to room temperature. The purpose of the aging treatment is to promote the precipitation and growth of nano-scale intermetallic compounds in the high-speed steel material, thereby improving the toughness and stability of the material.
[0030] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0031] 1) The high-speed steel material provided by the present invention is based on the synergistic effect between the various components. The intermetallic compounds generated in situ during the aging process have a coherent or semi-coherent relationship with the matrix, which can effectively strengthen the hardness of the material. The added Cr, Al and Si elements can form a dense oxide film structure with the Fe matrix, further improving the high-temperature oxidation resistance of the material. The rare earth elements Ce and Sc can effectively absorb impurities such as oxygen and sulfur, activate sintering, and purify grain boundaries, thereby effectively improving the high-temperature stability and toughness of the material.
[0032] 2) The room temperature peak hardness of the high-speed steel material provided by the present invention is 85-87HRA, the bending strength is 2800-3500MPa, and the impact toughness is 10-15J / cm 2 , the thermal conductivity at 700℃ is 45-50W / (m·K), the high temperature hardness at 800℃ is 81-83.5HRA, the hardness after aging at 600℃ for 200h is 82-85HRA, and the thermal expansion coefficient is 20-30% lower than that of 310S stainless steel. At the same time, the high-speed steel of the present invention can adjust the corresponding properties through the heat treatment process. For example, by aging at 900℃ for 3h, the impact toughness can be increased to 60-80J / cm2 That is, the high-speed steel of the present invention has the characteristics of high hardness, excellent thermal conductivity and small thermal expansion coefficient, and can achieve comprehensive performance optimization.
[0033] 3) The high-speed steel material described in the present invention can quickly transfer the heat of the heating pipe, reduce its load power, and increase the overall service life of the heating system; it has excellent dimensional stability when serving at high temperatures for a long time, can maintain high hardness and high strength, and reduce creep deformation, thereby improving the accuracy and production efficiency of the hot bending system. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope microstructure picture of Example 1;
[0035] Figure 2 This is a scanning electron microscope microstructure picture of comparative example 1. DETAILED DESCRIPTION
[0036] For a better understanding of the present invention, the present invention is further described below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0037] Among the following raw materials, the D50 particle size of the metal powder is 1-10 μm, and the particle size of the Ce powder and the Sc powder is 200-400 mesh.
[0038] In the following cases, the ball milling medium is all anhydrous ethanol, and based on the raw material powder, the amount of ball milling medium is 0.8 mL / g; the ball milling speed is 300 r / min.
[0039] Example 1
[0040] (1) Ultrasonic dispersion of raw materials
[0041] 1.4wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0042] (2) High-energy ball milling of raw materials
[0043] 0.3wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0044] (3) Pressing
[0045] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0046] (4) Vacuum sintering
[0047] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1350°C at a rate of 8°C / min, the holding time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0048] (5) Heat treatment
[0049] The sintered blank was placed in a vacuum quenching furnace for solution treatment at a temperature of 1220°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment was performed in a nitrogen-protected atmosphere furnace at a temperature of 800°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine was obtained.
[0050] Example 2
[0051] (1) Ultrasonic dispersion of raw materials
[0052] 1.0wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0053] (2) High-energy ball milling of raw materials
[0054] 0.4wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0055] (3) Pressing
[0056] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0057] (4) Vacuum sintering
[0058] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1330°C at a rate of 8°C / min, the heat preservation time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0059] (5) Heat treatment
[0060] The sintered blank was placed in a vacuum quenching furnace for solution treatment at a temperature of 1210°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment was performed in a nitrogen-protected atmosphere furnace at a temperature of 800°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine was obtained.
[0061] Example 3
[0062] (1) Ultrasonic dispersion of raw materials
[0063] 0.5wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0064] (2) High-energy ball milling of raw materials
[0065] 0.3wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 85h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0066] (3) Pressing
[0067] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0068] (4) Vacuum sintering
[0069] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1300°C at 8°C / min for 3 hours. The pressed green body was cooled to room temperature with the furnace to obtain a sintered green body.
[0070] (5) Heat treatment
[0071] The sintered blank was placed in a vacuum quenching furnace for solution treatment at a temperature of 1190°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment was performed in a nitrogen-protected atmosphere furnace at a temperature of 750°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine was obtained.
[0072] Example 4
[0073] (1) Ultrasonic dispersion of raw materials
[0074] 1.5wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0075] (2) High-energy ball milling of raw materials
[0076] 0.3wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0077] (3) Pressing
[0078] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0079] (4) Vacuum sintering
[0080] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1380°C at a rate of 8°C / min, the heat preservation time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0081] (5) Heat treatment
[0082] The sintered blank was placed in a vacuum quenching furnace for solution treatment at a temperature of 1270°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment was performed in a nitrogen-protected atmosphere furnace at a temperature of 850°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine was obtained.
[0083] Example 5
[0084] (1) Ultrasonic dispersion of raw materials
[0085] 0.9wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0086] (2) High-energy ball milling of raw materials
[0087] 0.3wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0088] (3) Pressing
[0089] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0090] (4) Vacuum sintering
[0091] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1350°C at a rate of 8°C / min, the holding time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0092] (5) Heat treatment
[0093] The sintered blank is placed in a vacuum quenching furnace for solution treatment at a temperature of 1200°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment is carried out in a nitrogen-protected atmosphere furnace at a temperature of 800°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine is obtained.
[0094] Comparative Example 1
[0095] The preparation process adopted in this comparative example is exactly the same as that adopted in Example 1, and the only difference is the ingredients.
[0096] Comparative Example 2
[0097] The preparation process adopted in this comparative example is exactly the same as that adopted in Example 1, and the only difference is the ingredients.
[0098] Comparative Example 3
[0099] The preparation process adopted in this comparative example is exactly the same as that adopted in Example 1, and the only difference is the ingredients.
[0100] Comparative Example 4
[0101] The preparation process adopted in this comparative example is exactly the same as that adopted in Example 1, and the only difference is the ingredients.
[0102] Comparative Example 5
[0103] (1) Ultrasonic dispersion of raw materials
[0104] 1.4wt.% nickel-plated graphene raw material was added to anhydrous ethanol and ultrasonically vibrated for 30 minutes (ultrasonic power was 150W), and then the remaining metal elements and rare earth element powders weighed according to the ratio were added, and ultrasonically vibrated together for 30 minutes to obtain a uniformly dispersed mixed powder anhydrous ethanol solution.
[0105] (2) High-energy ball milling of raw materials
[0106] 0.3wt.% carbon black and 5wt.% paraffin molding agent were added to the anhydrous ethanol solution of the mixed powder in step (1), and then placed together in a ball milling jar that could be protected by argon for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0107] (3) Pressing
[0108] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0109] (4) Vacuum sintering
[0110] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1250°C at a rate of 8°C / min, the heat preservation time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0111] (5) Heat treatment
[0112] The sintered blank is placed in a vacuum quenching furnace for solution treatment at a temperature of 1200°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment is carried out in a nitrogen-protected atmosphere furnace at a temperature of 800°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine is obtained.
[0113] Comparative Example 6
[0114] (1) High-energy ball milling of raw materials
[0115] According to the ratio, metal powder, rare earth powder and nickel-plated graphene raw material, as well as additionally added 0.3wt.% carbon black and 5wt.% paraffin molding agent, were placed in a ball milling jar that could be protected by argon gas for wet ball milling. The ball milling medium was anhydrous ethanol, the amount was 0.8mL / g, the ball-to-material ratio was 5:1, the ball milling speed was 300r / min, and the ball milling time was 80h. After the ball milling, it was dried in a vacuum drying oven, the temperature was set to 82°C, and the drying time was 5h.
[0116] (2) Pressing
[0117] The mixed powder after drying in step (2) is sieved through 40 meshes and then cold-molded at a pressing pressure of 150 MPa to obtain a compact.
[0118] (3) Vacuum sintering
[0119] The pressed green body was placed in a vacuum sintering furnace for vacuum sintering. The vacuum degree was controlled at less than 0.01 Pa. The temperature was raised from room temperature to a maximum sintering temperature of 1350°C at a rate of 8°C / min, the holding time was 3h, and the green body was cooled to room temperature to obtain a sintered green body.
[0120] (5) Heat treatment
[0121] The sintered blank was placed in a vacuum quenching furnace for solution treatment at a temperature of 1220°C for 1 hour, and then cooled to room temperature by gas quenching. Subsequently, an aging treatment was performed in a nitrogen-protected atmosphere furnace at a temperature of 800°C for 4 hours. Thus, the high-speed steel material for the heating plate of the hot bending glass machine was obtained.
[0122] The raw material composition ratios in the examples and comparative examples provided by the present invention are shown in Table 1.
[0123] Since the mechanical properties of the high-speed steel material described in the present invention are related to the heat treatment process, for a unified comparison, the peak aging process is used to compare the room temperature hardness, bending strength and impact toughness performance; high temperature hardness refers to the real-time test hardness value at 800℃ for 20 minutes. Table 2 shows the performance test results of the embodiment and the comparative example.
[0124] Table 1 Component mass percentage (wt.%) of the embodiments and comparative examples
[0125] Co Mo W Cr Al Ni Si V Ta Ce Sc Graphene Fe Example 1 25 15 3 9 8 7 1.8 0.7 0.5 0.2 0.2 1.4 Bal. Example 2 21 12 2 7 6 7 1.6 0.6 0.6 0.2 0.2 1.0 Bal. Example 3 15 9 1 5 5 6 1.5 0.5 0.5 0.1 0.1 0.5 Bal. Example 4 27 13 4 10 7 7 2 0.8 0.8 0.3 0.2 1.5 Bal. Example 5 18 10 5 8 7 7 1.7 0.5 0.6 0.2 0.2 0.9 Bal. Comparative Example 1 25 15 3 9 8 7 1.8 0.7 0.5 0.2 0.2 0 Bal. Comparative Example 2 25 15 3 9 8 7 1.8 0.7 0.5 0.2 0.2 2.0 Bal. Comparative Example 3 21 12 2 7 6 7 1.6 0.6 0.6 0 0 1.0 Bal. Comparative Example 4 25 15 3 13 10 10 1.8 0.7 0.5 0.2 0.2 1.4 Bal. Comparative Example 5 25 15 3 9 8 7 1.8 0.7 0.5 0.2 0.2 1.4 Bal. Comparative Example 6 25 15 3 9 8 7 1.8 0.7 0.5 0.2 0.2 1.4 Bal.
[0126] Table 2 Performance test results of embodiments and comparative examples
[0127]
[0128] It can be seen from the performance results in Table 2 that, compared with the traditional powder high-speed steel ASP30 and 310S stainless steel, the high-speed steel material prepared by the embodiment of the present invention has excellent high-temperature hardness and tempering resistance, that is, it can maintain excellent organizational and dimensional stability when used at high temperatures; at the same time, the large thermal conductivity can accelerate heat transfer, which is beneficial to reduce energy consumption during hot bending and improve the uniformity of glass heating. That is, the high-speed steel material prepared according to the material composition and preparation method of the present invention can improve production accuracy and production efficiency compared with the original heating plate material 310S stainless steel, and has great application prospects. The comparative examples that are not within the material composition range or process range of the present invention have performance degradation due to defects such as unreasonable composition design, uneven mixing, and low sintering density.
[0129] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A creep-resistant and highly thermally conductive graphene-modified high-speed steel material, characterized in that: The high-speed steel material comprises the following elements in percentage by mass: Co 15-30%, the total amount of Mo and W is 10-20% and the W content is less than 8%, Cr 5-10%, Ni 5-7%, Al 5-8%, Si 1.5-2%, V0.5-1%, Ta 0.5-1%, Ce 0.1-0.3%, Sc 0.1-0.2%, graphene is 0.5-1.5%, and the balance is iron; the high-speed steel material comprises an in-situ strengthening phase composed of an intermetallic compound and highly dispersed graphene; The intermetallic compound is an A7B6 type and / or AB2 type intermetallic compound; The preparation process of the high-speed steel material is as follows: dispersing graphene in a ball milling medium, adding the remaining metal element powder to continue dispersing, and then ball milling and drying with an auxiliary agent in sequence to obtain a mixture; and screening, cold pressing, sintering and heat treating the mixture in sequence to obtain the mixture.
2. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The high-speed steel material contains the following elements in mass percentage: Co 18-27%, the total amount of Mo and W 13-18% and the W content is less than 6%, Cr 7-10%, Ni 5-7%, Al 6-8%, Si 1.5-2%, V 0.5-1%, Ta 0.5-1%, Ce 0.1-0.3%, Sc 0.1-0.2%, graphene 1-1.5%, and the balance is Fe.
3. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The dispersion method is ultrasonic dispersion, and the conditions are: ultrasonic power is 100-200W, and the time is 20-40min; the ball milling medium is at least one of water, ethanol, propanol and petroleum ether.
4. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 3, characterized in that: The ball milling medium is ethanol; the ball milling method is wet high-energy ball milling, and the conditions are: under a protective atmosphere, the ball-to-material ratio is 4-7:1, the rotation speed is 240-340 r / min, and the time is 72-96 h; the protective atmosphere is high-purity nitrogen and / or high-purity argon.
5. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The additives include carbon black and a molding agent, wherein the amount of the carbon black added is 0.2-0.5% of the mass percentage of the mixture; the molding agent is at least one of paraffin, PEG and PVB; and the amount of the molding agent added is 3-6% of the mass percentage of the mixture.
6. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The particle size of the material obtained by sieving the mixed material is ≤40 mesh; the pressure of the cold pressing is 100~200MPa.
7. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The sintering is programmed temperature-raising vacuum sintering, and the sintering conditions are: heating from room temperature to 1300-1400° C. at 5-10° C. / min, keeping the temperature for 2-4 hours, and the vacuum degree ≤0.01 Pa.
8. The creep-resistant and highly thermally conductive graphene-modified high-speed steel material according to claim 1, characterized in that: The heat treatment includes solution treatment and aging treatment; the conditions of the solution treatment are: at 1150-1250°C, keep warm for 0.5-1.5h, and cool to room temperature by gas quenching; the conditions of the aging treatment are: under a protective atmosphere, the temperature is 700-1000°C, the time is 3-5h, and the furnace is cooled to room temperature.
Citation Information
Patent Citations
Preparation method of graphene composite high speed tool steel
CN109554628A
High-speed steel and preparation method and application thereof
CN114574788A
Cited By
Preparation method of high-content graphene sheet toughened high-speed steel
CN118062836A